USED IN THE WORK "KISASI RABGUZI". ANALYSIS OF AUXILIARY WORDS (Scientific journal of the Fergana State University, 2024)
The article analyzes the auxiliaries used in the work "Qisasi Rabguzi" written by Rabguzi, the son of Nasiruddin Burkhaniddin, which reflects the characteristics of the old Uzbek language. Nasiruddin Rabguzi was from Rabati Oguz, Khorezm, and lived at the end of the 13th century and the beginning of the 14th century. Only the writer's work "Qisasi Rabguzi" has survived to us, and it is considered the first major work written in prose in the Turkish language, and later became famous under the name "Qisasul-anbiyoyi Turki". Many assistants of the old Uzbek language participated in the work, and some of them have fallen out of use today. The difference between auxiliaries and words with independent meaning is not only that auxiliaries do not have an independent lexical meaning, but that the lexical meaning of auxiliaries has a certain characteristic, which makes them independent words. It appears only when it is attached to them. The transition of independent words to auxiliaries leads to changes in their lexical and grammatical features. Since auxiliaries are a grammatical category, the appearance of auxiliaries in a language is an element of grammar. The expansion of the group of assistants in Turkic languages, including Uzbek, dates back to the 12th-13th centuries. The widespread use of auxiliary words in the work "Qisasi Rabguzi" written on the basis of a rare example of the universal language confirms the correctness of the above opinions, and in turn, their study is the history of the Uzbek language and the present sheds light on some theoretical views of the Uzbek language.